The health effects of smoking bans: Evidence from German hospitalization data. (18th July 2018) - Kvasnicka, Michael; Siedler, Thomas; Ziebarth, Nicolas R.
Abstract: This paper studies the short‐term impact of public smoking bans on hospitalizations in Germany. It exploits the staggered implementation of smoking bans over time and across the 16 federal states along with the universe of hospitalizations from 2000 to 2008 and daily county‐level weather and pollution data. Smoking bans in bars and restaurants have been effective in preventing 1.9 hospital admissions (−2.1%) due to cardiovascular diseases per day, per 1 million population. We also find a decrease by 0.5 admissions (−6.5%) due to asthma per day, per 1 million population. The health prevention effects are more pronounced on sunny days and days with higher ambient pollution levels.